Faktor-faktor yang Mempengaruhi Ketepatan Waktu Penyampaian Laporan Keuangan pada Perusahaan Manufaktur - Jeprin Ujung; Delilah Delilah; Arie Pratania Putri (Universitas Sarjanawiyata Tamansiswa, 2022)
This research aims to examine the influence of the audit committee, KAP reputation, auditor turnover and company size on the timeliness in submitting financial statements. The research was carried out in the manufacturing sector which was included in the IDX list from 2017 to 2019. The procedure for data analysis was logistic regression and a significance level of 5% (0.05). The research population was 195 companies and purposive sampling was used in sample collection. So that the total sample obtained is 102 industries. Results Based on the research, it was revealed that auditor turnover proved a significant effect but three other reasons including audit committee, auditor turnover and company size had not been able to prove a significant effect